Phage-Mediated Immune Evasion and Transmission of Livestock-Associated Methicillin-Resistant Staphylococcus aureus in Humans - Raphael N. Sieber; Tinna R. Urth; Andreas Petersen; Camilla H. Møller; Lance B. Price; Robert L. Skov; Anders R. Larsen; Marc Stegger; Jesper Larsen (Emerging Infectious Diseases, 2020)
Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) can acquire phage-encoded immune modulators, such as the immune evasion cluster (IEC), which protects bacteria from components of the human innate immune system, and the enzyme TarP, which protects against antibody-mediated immune recognition. We used whole-genome sequencing and epidemiologic investigations to study the effects of IEC- and tarP-harboring phages on household transmission of LA-MRSA in North Denmark Region during 2004–2011. We reviewed information about all patients throughout Denmark who experienced LA-MRSA infection during 2007–2018 to determine whether IEC is associated with increased spread into the general population. Horizontal acquisition of IEC in the human host was associated with increased household transmission of LA-MRSA and spillover into the community and healthcare settings, whereas we found no evidence to suggest that IEC-positive LA-MRSA isolates have become self-sustainable in the general population. By contrast, TarP did not seem to influence household transmission of LA-MRSA.